Relasi Kuasa Pascareformasi dalam Pengelolaan Resor Wisata Nusa Dua - I Gusti Ketut Purnaya (Universitas Udayana, 2015)
This article analyses the power relations between threestakeholders involved in the management of the NusaDua Tourism Resort, Bali in the seventeen years after thereformation era, between 1998 to the present. It was chosenbecause after the reformation era, there have been changed inthe nature of power relations among the three stakeholders inthe region, that is between the government (BTDC), investor(hotel manager), and local communities. This study uses thetheory of hegemony, the discourse of power/ knowledge, andcommunication actions was applied eclectic considering thesub-topics discussed related to each other. The analysis ofthe power relations was strengthened by the analysis of thesubtopics of ideologies as a contributing factor to the natureof power relation and the strategy of each stakeholder wastaking in defining their relations to each others. The studyshows that the relation of power between BTDC and the localpeople had changed drastically since the reformation era,from the hegemonic into the negotiative which then changedinto the oppositional relation. The article concludes thatsocial and political situation in Bali gave significant impactsto the nature of relationship between tourism stakeholdersin Nusa Dua.